Os efeitos dos investimentos públicos e privados em capitais físicos e humano sobre o produto per capita dos municípios da região sul do Brasil : uma análise em painéis de dados dinâmicos, 1999-2004 - Kroth, Darlan Christiano (2007)
The objective of this paper is to measure in a dynamic way the contributions of human and physical capital to the per capita output of the Brazilian southern municipalities during 1999 - 2004. This paper innovates in two aspects regarding the reviewed literature. The first aspect is related to the variables human and physical capital. The human capital was built according to the methodology proposed by Koman and Marin (1999). The investment in physical capital was obtained from four sources: public investment made by the governments at municipal, state and federal levels and private ones made through loans from the banking system. However, the investments in physical capital expansion made with own resources were not available, omitted variable. The second aspect regards the econometric technique. The paper use the GMM (Generalized Method of Moments) proposed by Blundell and Bond (1998a) to compensate the omitted variable problem and the reverse causality accruing from output per capita to investment in capitals. The main results are that the investments in human and physical capital made by the governments had a significant influence on the output per capita. The human capital showed to be the most important one for the period analyzed. The private investments made through loans from the banking system were not significant.